Common and less well-known upper-limb injuries in elite tennis players - Shannon, N.; Cable, B.; Wood, T.; Kelly, J. (Current Sports Medicine Reports, 2020)
A recent increase in epidemiology studies on injuries in elite tennis players has helped to shed light on the types of injuries these athletes sustain. This article reviews the common upper-limb injuries in elite players and includes less well known, but important, injuries. A search was conducted to identify current relevant studies involving elite tennis players. Injury frequency rates, injuries by regions, and types of injuries together with a list of commonly reported injuries in the upper limb were established. This list was then reviewed and refined by a sports medicine physician who cares for elite tennis players to include both those injuries of the upper limb that are common and those that are less well known but still important and frequently encountered. Common injuries include internal shoulder impingement, rotator cuff pathology, labral tears, elbow tendinopathies, as well as extensor carpi ulnaris tendinopathies and subluxation. Posterior shoulder instability, distal humeral bone stress, elbow medial collateral ligament, and nondominant wrist ulnar collateral ligament injuries are not commonly reported injuries, but they are of significant clinical importance.